A new ultra violet-visible spectrophotometric method for quantitative determination of acrylamide via hydrolysis process - Chong Y.-M.; Ahmad M.; Heng L.Y. (Malaysian Society of Analytical Sciences, 2024)
Indexed by SCOPUS